Deepwater Horizon oil spill - Knutson, Julie (21st century skills library. Unnatural disasters., 2021)
Explores the causes and consequences of the BP Deepwater Horizon oil spill in the Gulf of Mexico in 2010. Examines the impact of the oil spill on people, the environment, and oil drilling practices. Includes color photographs, a timeline, a glossary, and additional resources.